Neuroprotective potential of quercetin in Alzheimer’s disease: targeting oxidative stress, mitochondrial dysfunction, and amyloid-β aggregation - Adnan, Mohd; Siddiqui, Arif Jamal; Bardakci, Fevzi; Surti, Malvi; Badraoui, Riadh; Patel, Mitesh (Frontiers in Pharmacology, 2025)
IntroductionAlzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by amyloid-beta (Aβ) peptide accumulation, oxidative stress, mitochondrial dysfunction and cholinergic deficits, all of which contribute to neuronal damage and cognitive decline.MethodsThis study investigated the neuroprotective potential of quercetin, a natural flavonoid, in human neuroblastoma SH-SY5Y cells exposed to Aβ-induced toxicity. Various assays were conducted to evaluate cell viability, reactive oxygen species (ROS) levels, mitochondrial membrane potential (ΔΨm), acetylcholinesterase (AChE) activity and Aβ aggregation.ResultsQuercetin significantly enhanced cell viability and reduced oxidative stress by lowering intracellular ROS levels. It preserved mitochondrial integrity by stabilizing ΔΨm and inhibited AChE activity, thereby supporting cholinergic function. Additionally, quercetin reduced Aβ aggregation and the formation of toxic amyloid fibrils.DiscussionThese findings suggest that quercetin confers neuroprotection by targeting multiple pathological mechanisms involved in AD, including oxidative stress, mitochondrial dysfunction, AChE activity and Aβ aggregation. Quercetin demonstrates promise as a natural therapeutic agent for the treatment of AD. However, further in-vivo investigations and clinical studies are warranted to validate these findings and explore its translational potential.